PCLN-07. A 3D HYDROGEL CULTURE SYSTEM FACILITATES STUDY OF PRIMARY PEDIATRIC LOW-GRADE GLIOMA CELLS IN VITRO. Issue 2 (22nd June 2018) - Wright, Karen D; Chadwick, Emily; Rota, Christopher; Brown, Alexander; Stockdale, Linda; Kieran, Mark W; Ligon, Keith; Goumnerova, Liliana; Lauffenburger, Douglas; Griffith, Linda; Segal, Rosalind
Abstract: Gliomas are the most common solid tumor of childhood and while children with low grade gliomas (LGGs) are likely to survive their disease, their course is complicated by significant treatment-related neurocognitive and endocrinological sequelae. Few accurate preclinical LGG models exist, thereby limiting development and testing of novel targeted agents. We developed a 3D, hydrogel-based co-culture system utilizing mouse astrocytes to support growth of primary human pediatric LGG cells in vitro. This tunable hydrogel system recapitulates many features of brain extracellular matrix, while the co-cultured astrocytes provide growth factors and other components normally present in vivo. In this system, patients' tumor cells are dissociated, and functionalized polyethylene glycol-based hydrogels are produced to surround tumor cells. These tumor-containing hydrogels are then placed adjacent to adherent layers of primary mouse astrocytes and the co-cultures grown for an extended period of time. Using this system, multiple types of human LGG cells and other pediatric tumor cells can be successfully cultured in hydrogels for up to one month. Moreover, these hydrogels can be enzymatically dissolved, releasing tumor cells to passage into new gels. Fluorescent 5-ethynyl-2'-deoxyuridine labeling followed by confocal microscopy of co-cultures reveals viable, proliferating cell clusters even one month later. While high grade gliomas in this setting proliferate rapidly, cultured LGG cells proliferate slowly, much like their original tumor counterparts. These methods can be used to provide patient-specific avatars to identify the best personalized targeted therapies. Moreover, the system enables investigations of the brain tumor microenvironment as a modulator of tumor growth.